REINTERPRETASI DERAJAT LAKI-LAKI LEBIH TINGGI ATAS PEREMPUAN DALAM SURAT AL-BAQARAH/2: 228 - Naqiyah Mukhtar (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
There are various interpretations from some exegetes of the word darajah in verse 228 of al-Baqarah, that â€œa man has adarajah (superiority) to a woman.â€ Some of the interpretations of the word darajah according to mufassirs are physical, intelectual,psychological, leadership, material, and divorce. Although the verse contextually is about divorce but limited to the right of a husband toreturn (rujÃ»â€™) to his wife in the â€˜iddah period. Thus, the word darajah in this verse is an explanation to the previous sentences, so this wordhas to be understood in this context